Alteration of performance in a mouse model of Emery–Dreifuss muscular dystrophy caused by A-type lamins gene mutation. (15th March 2019) - Thomasson, Rémi; Vignier, Nicolas; Peccate, Cecile; Mougenot, Nathalie; Noirez, Philippe; Muchir, Antoine
Abstract: Autosomal Emery–Dreifuss muscular dystrophy (EDMD) is caused by mutations in the lamin A/C gene ( LMNA ) encoding A-type nuclear lamins, intermediate filament proteins of the nuclear envelope. Classically, the disease manifests as scapulo-humero-peroneal muscle wasting and weakness, early joint contractures and dilated cardiomyopathy with conduction blocks; however, variable skeletal muscle involvement can be present. Previously, we and other demonstrated altered activity of signaling pathways in hearts and striated muscles of Lmna H222P/H222P mice, a model of autosomal EDMD. We showed that blocking their activation improved cardiac function. However, the evaluation of the benefit of these treatments on the whole organism is suffering from a better knowledge of the performance in mouse models. We show in the present study that Lmna H222P/H222P mice display a significant loss of lean mass, consistent with the dystrophic process. This is associated with altered VO2 peak and respiratory exchange ratio. These results showed for the first time that Lmna H222P/H222P mice have decreased performance and provided a new useful means for future therapeutic interventions on this model of EDMD.